2012
DOI: 10.1071/an11054
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and fatty acid content of lamb meat from perennial pasture or annual pasture systems with supplements

Abstract: The present study investigated the effect of a perennial lucerne and phalaris pasture, or annual pasture with lucerne hay and a range of supplements provided as pellets (700 g/day) on Vitamin E and fatty acid content of skeletal muscle and oxidative stability of lamb meat post-farm gate. Treatments were lambs grazing perennial pasture only (PP); lambs grazing annual pasture with lucerne hay and oat grain pellet supplement (AP); AP with cracked flaxseed (AP+FS); and AP with flaxmeal (AP+FM). After 7 weeks of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 31 publications
6
38
2
Order By: Relevance
“…Thus, mixed diets of lamb meat should deposit more saturated fatty acids than grazed lamb meat. The PUFA content in muscle from the PG group was higher than that in muscle from the M group, which may be due to the nature of the forage (Dierking, Kallenbach, & Grün, ; Lourenco, Van, Vlaeminck, De, & Fievez, ; Ponnampalam, Burnett, Norng, Warner, & Jacobs, ). Pastures are naturally high in PUFAs, especially linolenic acid.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, mixed diets of lamb meat should deposit more saturated fatty acids than grazed lamb meat. The PUFA content in muscle from the PG group was higher than that in muscle from the M group, which may be due to the nature of the forage (Dierking, Kallenbach, & Grün, ; Lourenco, Van, Vlaeminck, De, & Fievez, ; Ponnampalam, Burnett, Norng, Warner, & Jacobs, ). Pastures are naturally high in PUFAs, especially linolenic acid.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, active ingredients (condensed tannins) in forage effectively reduce the activity of ruminal bacterial and inhibit rumen biohydrogenation, which increases the proportion of PUFAs in animal tissues (Hajji et al, ). Tannins can cause a reduction in Butyrivibrio proteoclasticus , which convert vaccenic acid to stearic acid, thereby potentially resulting in higher levels of PUFAs in the muscle of PG lambs (Faria et al, ; Lobón et al, ; Ponnampalam et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it must be stressed that in order to obtain data which reflects the variability of IMF levels and FA composition of commercially produced lamb in Australia, samples in this study were of unknown background, age and sex that were sampled at a commercial abattoir. As previous studies have demonstrated the impact of breed (Demirel, Ozpinar, Nazli, & Keser, 2006), genetics , diet (Ponnampalam, Burnett, Norng, Warner, & Jacobs, 2012), production system (Ponnampalam, Butler, Jacob, et al, 2014), muscle sampled (Ponnampalam et al, 2010), sample location (Wood et al, 2008), age (Oriani et al, 2005) gender, carcase weight and fat score (Kosulwat, Greenfield, & James, 2003) on FA composition it is not useful to directly compare the FA composition found in the current study with established literature where these factors have been controlled. 1.5 2.5 3.5 4.5 5.5 6.5 7.5 Fatty acids (mg/ 100 g meat) Intramuscular fat (g/ 100 g meat) Fig.…”
Section: Intramuscular Fat and Fatty Acid Compositionmentioning
confidence: 85%
“…However, it is noteworthy that there was a reduction in 18:3 n-3 in lambs in response to the addition of soybean oil compared with control diets containing lucerne hay or ground lucerne pellet (Bessa et al, 2005). Recently Ponnampalam, Burnett, Norng, Warner, and Jacobs (2012) have indicated that adding quality lucerne hay in concentrate diets can be a nutritional strategy to lift the antioxidant potential and omega-3 fatty acid status of meat. Others have reported the proportion of 18:3 n-3 in heifers was increased Beaulieu, Drackley, and Merchen (2002) when compared between diets with and without soybean oil.…”
Section: Fatty Acid Composition and Nutritional Indicesmentioning
confidence: 92%